2004
DOI: 10.1159/000072493
|View full text |Cite
|
Sign up to set email alerts
|

Zaleplon Improves Sleep Quality in Maintenance Hemodialysis Patients

Abstract: Background/Aim: A recent survey has shown that insomnia is still a very common problem in maintenance hemodialysis (MHD) patients. The aim of the present study was to test the effects of zaleplon (ZAL), a new nonbenzodiazepine hypnotic drug, on the sleep quality of MHD patients with insomnia. Methods: The sleep quality was assessed by the Pittsburgh questionnaire in 10 patients (6 males/4 females) with insomnia on MHD; these patients underwent a randomized double-blind crossover study versus placebo (PLA). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 7 publications
0
26
2
1
Order By: Relevance
“…Depending on these findings we think that depression and poor sleep quality are closely associated with inflammatory conditions and malnutrition. In fact, in previous studies it was reported that higher malnutrition-inflammation scores were associated with the presence of moderate-to-severe depression and poor sleep and life quality in hemodialysis patients (26) patients who are good sleepers (21,22). We did not find such a relationship between sleep quality and hemoglobin, PTH, calcium, or phosphorus values.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Necontrasting
confidence: 74%
“…Depending on these findings we think that depression and poor sleep quality are closely associated with inflammatory conditions and malnutrition. In fact, in previous studies it was reported that higher malnutrition-inflammation scores were associated with the presence of moderate-to-severe depression and poor sleep and life quality in hemodialysis patients (26) patients who are good sleepers (21,22). We did not find such a relationship between sleep quality and hemoglobin, PTH, calcium, or phosphorus values.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Necontrasting
confidence: 74%
“…At a dose of 10 mg (5 mg if aged >65 years), there was significant improvement in the total score of sleep quality versus placebo ( P < 0.03) without significant adverse effects. 21 …”
Section: Sleep Disordersmentioning
confidence: 99%
“…A multitude of causes including anemia, blood urea levels, plasma creatinine levels, parathyroid hormone (PTH) concentrations, increased blood pressure, quality of life, and illness intrusiveness may contribute to sleep disturbances in patients on maintenance hemodialysis (Hanly et al, 2003;Iliescu et al, 2004;Sabbatini et al,2003). Furthermore, there is a positive correlation between sleep disturbances and increased morbidity and mortality related to cardiovascular disease and infectious complications, the 2 major causes of death in hemodialysis patients (De Santo et al, 2005).…”
Section: Related Factors With Sleep Problems In Hemodialysis Patientsmentioning
confidence: 99%
“…The Pittsburgh Sleep Quality Index, the Epworth Sleepiness Scale, and the Berlin Questionnaire are most frequently applied. Results derived from these questionnaires are limited by the subjective perception/sincerity of the patients, and thus are an imperfect substitute for more objective research methods on sleep in patients with chronic uremia (Chen et al, 2006;Iliescu et al, 2003;Mollaoglu & Mollaoglu, 2009;Sabbatini et al, 2003). Researchers have documented that ESRD patients reported significantly poorer subjective quality of sleep in comparison to the general population (Holley et al, 1992;Parker, 2005).…”
Section: Sleep Quality and Evaluation Of Sleep In Hemodialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation